Molecular Characterization and Antibiogram of Pseudomonas aeruginosa Isolated from Fish Sold in Markets of Tirupati, India: Molecular characterization and antibiogram of Pseudomonas aeruginosa - Sowmya R; Jagadeesh Babu A.; Chinta, Siva Swetha; Sreedevi B.; Suresh Y.; Vinayaka Siddhartha P.; Madhava Rao T. (Fishery Technology, 2024)
Pseudomonas aeruginosa is an emerging opportunistic pathogen and is one of the pathogens in the acronym ESKAPE representing a global threat to human health associated with antimicrobial resistance. The present study aimed for molecular characterization, virulence gene profiling and antimicrobial resistance studies of P. aeruginosa isolated from 200 fish samples collected from different fish markets in Tirupati, Andhra Pradesh, India. Of the 200 fish samples screened, 30.5% were confirmed as P. aeruginosa by PCR, targeting the 16S rRNA gene. Among the positive isolates, it was found that 70.4% and 75.4% of the isolates harbored toxA and exoS virulence markers, respectively. All 61 P. aeruginosa isolates recovered were phenotypically characterized for antimicrobial resistance patterns by the disc diffusion method. The study has found 100% resistance against erythromycin followed by 98.4% resistance to amoxicillin, 91.8% resistance against tetracycline, 88.5% resistance to vancomycin and cotrimoxazole, 45.9% resistance to ciprofloxacin, 44.2% resistance against cefepime and 9.9% resistance to gentamicin. The MAR indices were in the range from 0.5 to 1.0. The prevalence of multiple antibiotic resistance of P. aeruginosa harboring virulence genes in fish can pose a serious threat and hazard to public health through the consumption of raw or undercooked fish.